Utilization of partograph and associated factors among obstetric caregivers in Ethiopia: a systematic review and meta-analysis - Ayele, Mulat; Lake, Eyob Shitie; Yilak, Gizachew; Kumie, Getinet; Abate, Biruk Beletew; Zemariam, Alemu Birara; Tilahun, Befkad Derese (Frontiers in Global Women's Health, 2025)
IntroductionEffective use of the partograph is crucial in identifying abnormal labor (prolonged and obstructed labor) and taking appropriate actions. However, in Ethiopia, the prevalence of obstructed labor is much higher at 11.8% and contributes to 14.4% of the total maternal deaths due to underutilization of the partograph by obstetric caregivers. Although a previous systematic review and meta-analysis (SRMA) had been conducted, they were not representative on a national level as they included a limited number of studies and did not evaluate the current prevalence of partograph utilization beyond July 2019. Since then, there have been inconsistent studies assessing the proportion of partograph utilization and its associated factors. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence of partograph utilization and its associated factors in Ethiopia.MethodComprehensive literature searches were conducted in PubMed, Google Scholar, and HINARI from 1 September 2013 to 23 October 2023. A random-effects model was used to estimate pooled prevalence and adjusted odds ratio. Stata (version 11.0) was used to analyze the data. Cochrane I2 statistics were computed to assess heterogeneity among studies. A subgroup analysis was done based on the study region to minimize underlying heterogeneity. Funnel plot and Eggers test were conducted to assess publication bias.ResultOverall, 661 articles were retrieved, and finally, 23 studies were included in this systematic review, including 7,649 participants. The pooled prevalence of partograph utilization was 54.92% (95% CI: 43.38–66.45). The subgroup analysis showed that partograph utilization was highest in the Dire Dawa region and lowest in the Amhara region. Factors such as partograph training [adjusted odds ratio (AOR) = 3.63, 95% CI: 2.57–5.25], good knowledge about partograph (AOR = 2.63, 95% CI: 1.62–4.26), a favorable attitude toward partograph (AOR = 1.95, 95% CI: 1.35–2.82), partograph availability (AOR = 0.89, 95% CI: 2.24–6.61), and being in the midwifery profession (AOR = 0.09, 95% CI: 1.78–5.25) were significantly associated with partograph utilization.ConclusionThe pooled prevalence of partograph utilization in Ethiopia was low. Partograph training, good knowledge about partograph, favorable attitude toward partograph, partograph availability in the health facility, and being in the midwifery profession were significantly associated with partograph utilization.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier (CRD42023475818).